2009
DOI: 10.1016/j.molcel.2008.12.016
|View full text |Cite
|
Sign up to set email alerts
|

ING4 Mediates Crosstalk between Histone H3 K4 Trimethylation and H3 Acetylation to Attenuate Cellular Transformation

Abstract: Summary Aberrations in chromatin dynamics play a fundamental role in tumorigenesis, yet relatively little is known of the molecular mechanisms linking histone lysine methylation to neoplastic disease. ING4 (Inhibitor of Growth 4) is a native subunit of an HBO1 histone acetyltransferase (HAT) complex and a tumor suppressor protein. Here we show a critical role for the specific read-out of histone H3 trimethylated at lysine 4 (H3K4me3) by the ING4 PHD finger in mediating ING4 gene expression and tumor suppressor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
193
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(207 citation statements)
references
References 33 publications
12
193
1
1
Order By: Relevance
“…1C). The discrepancy between H3K4me3 and H3K79me1/2/3 suggests that H3K4me3 is affected by other pathways in addition to an H2Bub1-dependent pathway; these might include crosstalk with the lysine acetylations of H3 (Hung et al 2009), counter-correlation with H3R2 methylation (Guccione et al 2007), and several other related pathways. Clearly, the bidirectional pattern of H3K4me3 in the regions surrounding the TSS and the broader distribution of H2Bub1 in transcribed regions provide strong evidence that there is a discrepancy between H2Bub1 and H3K4me3.…”
Section: Trans-crosstalk Between H2bub1 and H3k79 Methylations Is Assmentioning
confidence: 99%
“…1C). The discrepancy between H3K4me3 and H3K79me1/2/3 suggests that H3K4me3 is affected by other pathways in addition to an H2Bub1-dependent pathway; these might include crosstalk with the lysine acetylations of H3 (Hung et al 2009), counter-correlation with H3R2 methylation (Guccione et al 2007), and several other related pathways. Clearly, the bidirectional pattern of H3K4me3 in the regions surrounding the TSS and the broader distribution of H2Bub1 in transcribed regions provide strong evidence that there is a discrepancy between H2Bub1 and H3K4me3.…”
Section: Trans-crosstalk Between H2bub1 and H3k79 Methylations Is Assmentioning
confidence: 99%
“…In support of this mechanism WDR5 knockdown, which depletes H3K4 methylation (48), attenuates the TSA-induced increase in H3K9ac levels at promoters (18). Other KATs are known to be recruited to H3K4me3 to induce histone acetylation; yeast Yng1 and Yng2, which recognize H3K4me3 via their plant homeo domain (PHD) fingers (49, 50), form part of the NuA3 and NuA4 KAT complexes, respectively (51,52), and mammalian ING4 links HBO1 acetyltransferase activity to H3 lysine-4 trimethylated nucleosomes (53,54).…”
Section: Cotargeting Of H3k4 Trimethylation and Dynamic Acetylation Tmentioning
confidence: 99%
“…ING4 was also co-purified with the HBO1/JADE histone acetyltransferase (HAT) complex that is involved in chromatin modification and activation of transcription in response to DNA damage [26]. The association between ING4 and H3K4me3 augments HBO1 acetylation activity on H3 tails and drives H3 acetylation at ING4 target promoters [12]. ING4 also co-localizes with Liprina1 in the lamellipodia of cells and inhibits cell spreading and migration, suggesting that ING4 has additional functions in the cytoplasm [3].…”
Section: Discussionmentioning
confidence: 99%
“…ING4 binds to p53 and p300, and enhances the transcription activity of p53 [8]. ING4 is a native subunit of an HBO1 histone acetyltransferase (HAT) complex that is required for normal cellular progression through S phase and histone H4 acetylation in vivo [12]. A recent study found that specific recognition of histone H3 trimethylated at lysine 4 (H3K4me3) by the ING4 PHD finger is critical for mediating ING4 tumor suppressor functions [13].…”
mentioning
confidence: 99%